A phenomenological investigation of Windhoek Senior Secondary school principals' perceptions and experiences of their leadership roles - Boys, Ben (Rhodes University, Faculty of Education, Department of Education, 2002)
Namibia, having been a former colony of South Africa, was equally subjected to apartheid laws and practices. Independence, achieved in March 1990, signaled the dawn of a new era of access, equity, quality and democracy in the Namibian education sector. A unified system of educational administration, management, and control was established. The whole educational corps, especially the principals of all our schools, is expected to implement this new system as agents of change. In terms of the vision for a new Namibia, therefore, school principals are seen as occupying positions of central importance. This notion resonates strongly with recent and contemporary leadership thinking. However, a number of concerns prevalent in schools - particularly, increasing student underperformance, worsening disciplinary problems, increasing teenage pregnancy and HIV/AIDS pandemic, teacher qualification, decreasing teacher motivation, lack of training including induction for principals, inadequate support from the top (lack of a support system) and insufficient parental involvement in school matters "“ make the task of running schools extremely challenging and increasingly complex. How do principals experience these challenges and deal with the complex situations? How do they perceive their role, particularly in light of national aspirations and leadership theory? These are questions I think need to be explored. My research goal was to gain an understanding of Windhoek senior secondary school principals' perceptions and experiences of their leadership role. My focus was on three purposively selected Windhoek senior secondary school principals representative of both the Namibian ethno-cultural diversity and gender. Data was collected through interviews. I found that the situations in which the principals found themselves during the pre- and post independent periods mainly determined their leadership style and behaviour, however, that did not deter their vision for the transformation of the society, as the ultimate objective and essence of their leadership. The appropriate practicing of their leadership role was being hampered by lack of induction and training, lack of a support system and insufficient parental involvement.
Keywords: School principals -- Namibia; Educational leadership -- Namibia